Chloride and sodium ion concentrations in saliva and sweat as a method to diagnose cystic fibrosis - Aline Cristina Gonçalves; Fernando Augusto Lima Marson; Regina Maria Holanda Mendonça; Carmen Sílvia Bertuzzo; Ilma Aparecida Paschoal; José Dirceu Ribeiro; Antônio Fernando Ribeiro; Carlos Emílio Levy (Brazilian Society of Pediatrics, 2019)
Objective: Cystic fibrosis diagnosis is dependent on the chloride ion concentration in the sweat test (≥ 60 mEq/mL - recognized as the gold standard indicator for cystic fibrosis diagnosis). Moreover, the salivary glands express the CFTR protein in the same manner as sweat glands. Given this context, the objective was to verify the correlation of saliva chloride concentration and sweat chloride concentration, and between saliva sodium concentration and sweat sodium concentration, in patients with cystic fibrosis and healthy control subjects, as a tool for cystic fibrosis diagnosis. Methods: There were 160 subjects enrolled: 57/160 (35.70%) patients with cystic fibrosis and two known CFTR mutations and 103/160 (64.40%) healthy controls subjects. Saliva ion concentration was analyzed by ABL 835 Radiometer® equipment and, sweat chloride concentration and sweat sodium concentration, respectively, by manual titration using the mercurimetric procedure of Schales & Schales and flame photometry. Statistical analysis was performed by the chi‐squared test, the Mann-Whitney test, and Spearman's correlation. Alpha = 0.05. Results: Patients with cystic fibrosis showed higher values of sweat chloride concentration, sweat sodium concentration, saliva chloride concentration, and saliva sodium concentration than healthy controls subjects (p‐value < 0.001). The correlation between saliva chloride concentration and sweat chloride concentration showed a positive Spearman's Rho (correlation coefficient) = 0.475 (95% CI = 0.346 to 0.587). Also, the correlation between saliva sodium concentration and sweat sodium concentration showed a positive Spearman's Rho = 0.306 (95% CI = 0.158 to 0.440). Conclusions: Saliva chloride concentration and saliva sodium concentration are candidates to be used in cystic fibrosis diagnosis, mainly in cases where it is difficult to achieve the correct sweat amount, and/or CFTR mutation screening is difficult, and/or reference methods for sweat test are unavailable to implement or are not easily accessible by the general population. Resumo: Objetivo: O diagnóstico da fibrose cística depende do valor da concentração de íons de cloreto no teste do suor (≥ 60 mEq/mL - reconhecido como o indicador‐padrão para o diagnóstico da doença). Além disso, as glândulas salivares expressam a proteína RTFC igualmente às glândulas sudoríparas. Nesse contexto, nosso objetivo foi verificar a correlação da concentração de cloreto na saliva e a concentração de cloreto no suor e entre a concentração de sódio na saliva e a concentração de sódio no suor em pacientes com fibrose cística e indivíduos controles saudáveis, como uma ferramenta para diagnóstico de fibrose cística. Métodos: Contamos com a participação de 160 indivíduos [57/160 (35,70%) com fibrose cística e duas mutações no gene RTFC conhecidas e 103/160 (64,40%) indivíduos controles saudáveis]. A concentração de íons na saliva foi analisada pelo equipamento ABL 835 da Radiometer® e a concentração de cloreto no suor e sódio no suor, respectivamente, por titulação manual utilizando o método mercurimétrico de Schales & Schales e fotometria de chama. A análise estatística foi realizada pelo teste qui‐quadrado, pelo teste de Mann‐Whitney e pela correlação de Spearman. Alpha = 0,05. Resultados: Os pacientes com fibrose cística apresentaram maiores valores na concentração de cloreto no suor, concentração de sódio no suor, concentração de cloreto na saliva e concentração de sódio na saliva do que os indivíduos‐controle saudáveis (valor de p < 0,001). A correlação entre as concentrações de cloreto na saliva e cloreto no suor mostrou Rho de Spearman (coeficiente de correlação) positivo = 0,475 (IC de 95% = 0,346 a 0,587). Além disso, a correlação entre concentração de sódio na saliva e concentração de sódio no suor mostrou Rho de Spearman positivo = 0,306 (IC de 95% = 0,158 a 0,440). Conclusões: A concentração de cloreto na saliva e a concentração de sódio na saliva são candidatas a ser usadas como diagnóstico de fibrose cística, principalmente em casos em que é difícil atingir a quantidade correta de suor, e/ou o exame da mutação RTFC é difícil e/ou o método de referência para o teste do suor não se encontra disponível ou não é de fácil acesso ao público em geral. Keywords: CFTR protein, CFTR mutation, Cystic fibrosis, Electrophysiology, Ionic concentration, Sweat test, Palavras‐chave: Proteína RTFC, Mutação no RTFC, Fibrose cística, Eletrofisiologia, Concentração iônica, Teste do suor